Comparative analysis of annual and monthly peak flow tendencies, considering two periods in north-central Chile - Pizarro, Roberto; García-Chevesich, Pablo; Balocchi, Francisco; Pino, Juan; Ibáñez, Alfredo; Sangüesa, Claudia; Vallejos, Carlos; Mendoza, Romina; Ingram, Ben; Sharp, Jonathan O (Tecnología y ciencias del agua, 2022)
It is essential to understand long-term trends associated with water resources in arid climates such as Chili’s to prepare and predict potential adverse implications of climate change in these already water-stressed regions. Trends in annual peak flows (instantaneous maximum flows) of the Coquimbo Region were studied through the Mann-Kendall statistical test (5 % error), considering the 1984-2014 period and, in a second analysis, extending the series to at least 29 % more (1976-2014). Results indicate that for the annual peak flows, in both periods, all analyzed series showed a tendency to decrease (80 % of them significantly in the 1984-2014 period and 29 % in the 1976-2014 period). In contrast, analysis of monthly peak flows revealed a more nuanced shift where 99 % of the series tended to decrease in the 1984-2014 period, with 46 % being significant. However, in the 1976-2014 period, 74 % of series tended to decrease, but only 12 % were significant. This decline in negative and significant trends after incorporating years before 1984 suggests that these situations have occurred previously. Finally, this variation in the significance level when considering different time lengths would evidence a cyclic process that influences the behavior of peak flows.